Anti-GPC3 antibody-modified sorafenib-loaded nanoparticles significantly inhibited HepG2 hepatocellular carcinoma - Tang, Xiaolong (Drug Deliv, 2018)
Sorafenib (SFB) has improved the treatment of hepatocellular carcinoma (HCC) and has fewer severe side effects than other agents used for that purpose. However, due to a lack of tumor-specific targeting, the concentration of the drug in tumor tissue cannot be permanently maintained at a level that inhibits tumor growth. To overcome this problem, we developed a novel SFB-loaded polymer nanoparticle (NP). The NP (a TPGS-b-PCL copolymer that was synthesized from ε-caprolactone and d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) via ring-opening polymerization) contains Pluronic P123 and SFB, and its surface is modified with anti-GPC3 antibody to produce the polymer nanoparticle (NP-SFB-Ab). The Ab-conjugated NPs had higher cellular uptake by HepG2 cells than did non-antibody-conjugated SPD-containing nanoparticles (NP-SFB). The NP-SFB-Ab also displayed better stability characteristics, released higher levels of SFB into cell culture medium, and was more cytotoxic to tumor cells than was non-targeted NP-SFB and free SFB. The NP-SFB-Ab downregulated expression of the anti-apoptosis molecule MCL-1, which led to polymerization of Bax and Bak in mitochondrial cytosol. The NP-SFB-AB also promoted the mitochondrial release of cytochrome C, resulting in cellular apoptosis. Moreover, the NP-SFB-Ab significantly inhibited the growth of HepG2 xenograft tumors in nude mice without producing obvious side effects. These findings suggest that NP-SFB-Ab is a promising new method for achieving targeted therapy of HCC.